The schemata of the stars - Paschos, E. A (World Scientific, 1998)
Includes bibliographical references and index.; Most of the knowledge of ancient Greek science survived through Byzantine codices. A short Byzantine article, extant in three manuscripts, contains advanced astronomical ideas and pre-Copernican diagrams; it presents improvements on ancient and medieval astronomy. This important book includes the edited version and translation of the text and analyzes its content. It surveys the development of astronomical models from Ptolemy to Byzantium and compares them mathematically with several works of Arab astronomers, as well as with the heliocentric system of Copernicus and Newton